Thermoelectric properties investigation of Tungsten carbide-filled poly (vinyl alcohol)/Polypyrrole ternary composites - Arslanturk, Gizem; Ugraskan, Volkan (TAYLOR & FRANCIS INC, 2024)
Many researchers have recently focused their attention on conductive polymer-based flexible thermoelectric (TE) materials. One of the most popular approaches for improving TE efficiency is the addition of inorganic components to conductive polymers. In this work, the TE properties of tungsten carbide-filled poly (vinyl alcohol)/polypyrrole (PVA/PPy/WC) ternary composites were examined for the first time. First, composites with varying WC weight ratios were produced by the solvent casting process. Scanning electron microscopy (SEM) investigations demonstrated the homogenous dispersion of WC particles in the composite structure, while X-ray diffraction (XRD) analyses determined the influence of WC addition on the crystal structure of the composite. The electrostatic interactions of each component were revealed by Fourier transform infrared-attenuated total reflectance spectroscopy (FTIR-ATR) and UV-vis studies. Additionally, with the addition of WC, the energy bandgap of PVA/PPy reduced from 5.71 eV up to 2.07 eV. From TE studies, it was obtained that the electrical conductivity of PVA/PPy increased from 3.35 x 10(-3) up to 58 Sm-1 with the addition of 30% WC, while the power factor (PF) of PVA/PPy increased from 8,6 x 10(-9) mu Wm(-1)K(-2) up to 1.71 x 10(-3) mu Wm(-1)K(-2). Both composite samples had negative Seebeck coefficients, which are typical of n-type conductors.
Keywords: Thermoelectric; composite; poly (vinyl alcohol); polypyrrole; tungsten carbide; OXIDE; PERFORMANCE; DEVICES; FILMS; Polymer Science